PENYELESAIAN PERSELISIHAN PHK PASCA BERLAKUNYA UNDANG-UNDANG CIPTA KERJA (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Indonesia is a unitary state with Pancasila as the state ideology. This has the consequence that all life arrangements in the unitary state of the Republic of Indonesia must be based on the values contained in Pancasila, including the order in industrial relations. This research is legal research in relation to academic activities. Disputes regarding layoffs are always related to the fulfillment of workers' rights, compensation or severance pay and the obligations of employers to fulfill their obligations. Industrial relations disputes arise because of differences of opinion that lead to conflict. Whether this is experienced by entrepreneurs or combinations of entrepreneurs and laborers or workers. Conclusion 1. there are quite significant differences in regulations regarding the resolution of employment termination disputes after the enactment of Law No. 11 of 2020 concerning Job Creation, 2. quite significant regulatory differences have an impact on cases of employment termination disputes which are in the process of being resolved legally